2011
DOI: 10.1002/adma.201101694
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design and Enhanced Biocompatibility of a Dry Adhesive Medical Skin Patch

Abstract: A new type of medical skin patch is developed that contains high‐density, mushroom‐like micropillars. Such dry‐adhesive micropillars are highly biocompatible, have minimized side effects, and provide reasonable normal adhesion strength. To arrive at optimal conditions for the dry adhesive skin patch, the proper design of various structural and material parameters of micropillars is investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
268
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(270 citation statements)
references
References 32 publications
2
268
0
Order By: Relevance
“…Recent studies on flexible mechanical and electrical sensing devices have demonstrated great potential in a wide range of applications, such as displays, 1,2 robotics, [3][4][5][6] in vitro diagnostics, [7][8][9] advanced therapies, 10,11 and energy harvesting. 2,[12][13][14] Such remarkable advances have been achieved through various solutions through the use of electrical active matrices on flexible rubberlike substrates to obtain various functions, such as high bendability, 15,16 ultrasensitivity, 7,17 transparency, 1,2,18-21 or wellestablished human-device interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on flexible mechanical and electrical sensing devices have demonstrated great potential in a wide range of applications, such as displays, 1,2 robotics, [3][4][5][6] in vitro diagnostics, [7][8][9] advanced therapies, 10,11 and energy harvesting. 2,[12][13][14] Such remarkable advances have been achieved through various solutions through the use of electrical active matrices on flexible rubberlike substrates to obtain various functions, such as high bendability, 15,16 ultrasensitivity, 7,17 transparency, 1,2,18-21 or wellestablished human-device interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior is mainly attributed to the enlarged 3D microtips of octopus‐like sucker that can increase effective contact area to a combining surface. Therefore, the suction stress (negative pressure effect for wet condition) and molecular interactions (van der Waals for dry surface or capillary interaction for wet condition) between two engaged surfaces are amplified 6, 8, 28. Likewise, the adhesive with CR of 0.93 exhibited the highest adhesion performances among other samples for peeling off in both dry and underwater conditions (see Figure S6 for details, Supporting Information).…”
mentioning
confidence: 99%
“…These two types of controllable adhesives were inspired by aphids and geckos, respectively. Although the natural adhesives, especially the gecko type, have motivated engineers to develop artificial smart/controllable adhesives using relatively simple structures in diverse applications including climbing robots [44], bio-medical systems [45] and many others, none of these materials offers the same combination of remarkable properties that the natural gecko adhesive does [46][47][48]. So far, no report exists in which the sophisticated natural adhesives were used for any practical applications.…”
Section: Introductionmentioning
confidence: 99%